Methanol (80%) leaf extract of Otostegia integrifolia Benth (Lamiaceae) lowers blood pressure in rats through interference with calcium conductance - Abel Degu; Abiy Abebe; Ephrem Engidawork (BMC, 2021)
Abstract Background Otostegia integrifolia Benth. (Lamiaceae) leaves are used to treat hypertension in Ethiopian folk medicine. However, the claim has so far not been investigated scientifically. Thus, the objective of this study was to evaluate the antihypertensive activity of 80% methanol leaf extract of O. integrifolia in animal model of hypertension and possible underlying mechanisms in isolated rat aorta. Methods Antihypertensive effect of various oral doses of the extract (250, 500 and 1000 mg/kg) was determined in fructose-induced hypertensive rats using the non-invasive tail-cuff method. Thoracic aortic strips of rats were isolated and suspended in organ bath, and the vasodepressor effect as well as the possible mechanism (s) of action were studied by means of isometric tension recording experiments ex vivo. Phytochemical analysis was also performed to suggest possible constituents related to the activity. Results Blood pressure was significantly lowered in a dose-dependent manner following extract administration, suggesting that the extract possesses antihypertensive activity. The extract also caused a dose-dependent relaxation of aortic strip precontracted with KCl at a concentration of 6.25-125 μg/L, with a maximum relaxation (100%) achieved at a cumulative concentration of 318.75 μg/ml. The relaxation mechanism was found to be independent of muscarinic receptors, prostanoids, histamine receptors, ATP dependent K+ channels, sarcoplasmic reticulum stored Ca2+ and the endothelium system. The extract shifted the Ca2+ concentration-response curve to the right similar to that caused by nifedipine, suggesting that vasorelaxation could possibly be mediated via calcium channel blockade. The extract was found to contain phenolic compounds (164.3 mg/g, expressed as gallic acid equivalents) and flavonoids (125.7 mg/g, expressed as quercetin equivalents). Conclusion The findings revealed that the plant is endowed with antihypertensive activity, providing evidence for its traditional use. The effect maybe, at least in part, due to dilation of blood vessels through blockade of Ca+ 2 channels mediated by phenolic and flavonoid constituents.